Systematic, active, contextual, technological, integrative (SAKTI) framework in the development of critical listening teaching materials - Yanti, Nafri; Yeti Mulyati; Dadang Sunendar; Vismaia S. Damaianti (UNIB Press, 2024)
This research is motivated by the limited availability of digital module teaching materials, especially in critical listening learning. This study aims to produce critical listening learning modules that are structured on the principles of systematic, active, contextual, technological, integrative (SAKTI). This principle is formulated by researchers from various critical listening learning theories and the development of teaching materials that are relevant to current needs. The digital teaching materials are arranged to contain materials, listening materials, exercises, and evaluations in one teaching material. The research was conducted by applying the research procedure proposed by Tomlinson in 2012. The module was developed using the Flip Pdf Professional Application Version 2.4.9.41, Quizzes, Canva, Google Form, Ms. Word, Dolby On, Nitro Pdf. The module consists of 3 main components, namely the introductory, core, and closing sections. This study uses R&D methods with stages Analysis, Design, Development, Implementation, & Evaluations. Based on the results of product trials, it is known that the use of the designed product provides several advantages, among which it makes the learning process practical, can be used anywhere and at any time, helps guided or independent learning, helps online and offline learning, encourages students to actively complete each stage of learning and can be a means of obtaining new information for students.